Studi literatur: Analisis sifat fisis air yang disimpan dalam qirbah berbahan kulit hewan (sapi, kambing, domba dan kelinci) - Mu’amanah, Rizky (Maliki Interdisciplinary Journal, 2024)
Qirbah is an Arabic term that refers to a vessel or drinking vessel made from tanned animal skin. Qirbah was used before the discovery of plastic or other materials as a portable drinking container. Qirbah can be made from tanned animal skin and sewn to form a pouch. So far, the skin commonly used for Qirbah is Cow, Goat, Sheep and Rabbit skin. The conclusion from various studies shows that qirbah made from rabbit skin is not ideal as a container for storing drinking water safely. Increased concentrations of heavy metals and high levels of bacteria can have a negative impact on human health. Meanwhile, Qirbah made from goat, sheep and cow leather has safe water quality and can be used as a water container.